(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Lipids constitute one of the major types of organic matter found in municipal wastewater. Many manufacturing, food processing and industrial facilities dispose of liquid waste into sewer lines. Liquid waste often contains fats, oils and grease and other organic contaminants which, over time, lead to clogs in pipes. The treatment of this problem is to clean pipes with caustic drain cleaners, mechanically rout the pipes or to replace the pipes completely. The second problem was the utilization of solid waste. JSC “Biocentras” suggest a very effective and innovative complex technology. Firstly, lipids from wastewater and from drain pipes surfaces are removing mechanically. Remained lipids and solid wastes were treated with a composition of active microorganisms. The novel composition is nonpoisonous, no corrosive, no caustic and ecologically advantageous. The invented technology ensures maximum results at the lowest cost in the shortest period of time.